Desalination of Groundwater Using Marble Filter - Mohd Akhir, Muhammad Fitri (International Journal of Integrated Engineering, 2019)
The world has changed tremendously in terms of human development, population growth, and climate change. An in-depth study of groundwater treatment is necessary to ensure water crisis such as water scarcity, industrial pollution, natural contamination and high-water demand can be handled in the future. Salinity problem is one of the most vital issues that needs to be taken care of. Instead of using membrane technology as the main filter, marble filter gives more contribution as low cost physical filtration treatment of saline groundwater (5.1Â±0.1ppt). The marble filter acts as the main filter and has been tested for two media sizes i.e. pebble and sand size. This filtration is free from chemical usage. Desalination results for marble in sand size at flowrate 0.011 l/s and temperature above 29oC shown very impressive results with 97.48% salinity removal. The retention time is approximately 1 hour 3 minutes. Both marble filter sizes efficiency reduced after 30 minutes of filtration.